Effects of jazz dance and concurrent training on psychological variables in menopausal women: A randomized controlled trial - Fausto D.Y.* (2024)
© The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2024.Purpose: To analyze the effect of two 16-week interventions with jazz dance and concurrent training compared to a control group on anxiety, depression, stress, mood, and the perspective of aging in menopausal women, after 1-month, post-intervention, and at the 6-month follow-up. Methods: 70 post-menopausal women (53.19 ± 3.39 years) randomized into 3 groups:intervention group with Jazz Dance (JD); intervention group with Concurrent Training (CT), and Control Group (CG). Both interventions lasted 16 weeks, with 60-min classes, JD with a frequency of two weekly classes, and CT three times a week. The intensity of the JD was progressive and according to the frequency of beats per minute of the songs. In CT, the aerobic an initial intensity of 60% of HRmax, reaching 90%, and resistance the volume of sets and loads increased progressively throughout the intervention. Questionnaires related to symptoms of anxiety and depression (Hospital Anxiety and Depression Scale); stress (Perceived Stress Scale); mood (Brunel Mood Scale); and aging perspective (Sheppard Inventory) were applied. Intention-to-treat (ITT) and protocol adherence analysis were performed. Results: In the protocol analysis, the JD showed improvements in anxiety and depressive symptoms after 1-month, which remained at the follow-up. The TC presented reduced anxiety and depressive symptoms after 16 weeks, which also remained at the follow-up. Considering stress, the CT showed improvements at all times and the JD post-intervention. As for mood, the CT presented reduced anger, mental confusion, and fatigue only after 1-month, and both exercise groups presented increased vigor at all times. Conclusion: Both interventions were beneficial, however dance showed immediate results for anxiety and depression, and concurrent training for stress. Considering mood, concurrent training was more effective for anger, mental confusion, and fatigue, while both interventions were effective for vigor. Registration: Brazilian Clinical Trials Registry (REBEC) RBR – 87ndrv.